A Halogenation Strategy for over 12% Efficiency Nonfullerene Organic Solar Cells. Issue 15 (30th January 2018) - Wang, Yanbo; Zhang, Yamin; Qiu, Nailiang; Feng, Huanran; Gao, Huanhuan; Kan, Bin; Ma, Yanfeng; Li, Chenxi; Wan, Xiangjian; Chen, Yongsheng
Abstract: Three acceptor–donor–acceptor type nonfullerene acceptors (NFAs), namely, F–F, F–Cl, and F–Br, are designed and synthesized through a halogenation strategy on one successful nonfullerene acceptor FDICTF (F–H). The three molecules show red‐shifted absorptions, increased crystallinities, and higher charge mobilities compared with the F–H. After blending with donor polymer PBDB‐T, the F–F‐, F–Cl‐, and F–Br‐based devices exhibit power conversion efficiencies (PCEs) of 10.85%, 11.47%, and 12.05%, respectively, which are higher than that of F–H with PCE of 9.59%. These results indicate that manipulating the absorption range, crystallinity and mobilities of NFAs by introducing different halogen atoms is an effective way to achieve high photovoltaic performance, which will offer valuable insight for the designing of high‐efficiency organic solar cells. Abstract : Through a halogenation strategy onto the end‐capping group in the FDICTF‐based small‐molecule acceptor, red‐shifted absorptions, increased crystallinities, and higher charge mobilities are achieved. The device based on F–Br with power conversion efficiency of 12.05% and remarkable FF of 76% is one of only a few organic solar cells with efficiencies over 12% reported to date.